2016
DOI: 10.1021/acsami.6b12947
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures Significantly Enhance Thermal Transport across Solid Interfaces

Abstract: The efficiency of thermal transport across solid interfaces presents large challenges for modern technologies such as thermal management of electronics. In this paper, we report the first demonstration of significant enhancement of thermal transport across solid interfaces by introducing interfacial nanostructures. Analogous to fins that have been used for macroscopic heat transfer enhancement in heat exchangers, the nanopillar arrays patterned at the interface help interfacial thermal transport by the enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 54 publications
4
43
0
2
Order By: Relevance
“…Kapitza conductance is extremely dependent on the structural details of the interface at the nanoscale since the characteristic dimensions are comparable to or less than the vibrational mean‐free paths. Nanostructuring at the interface has been efficiently used to tune the energy transport pathways across interfacial regions either by introducing roughness, nonplanar features, interface mixing, or by functionalizing the interface to alter the stiffness of the bonds …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Kapitza conductance is extremely dependent on the structural details of the interface at the nanoscale since the characteristic dimensions are comparable to or less than the vibrational mean‐free paths. Nanostructuring at the interface has been efficiently used to tune the energy transport pathways across interfacial regions either by introducing roughness, nonplanar features, interface mixing, or by functionalizing the interface to alter the stiffness of the bonds …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…Experimental works have demonstrated that nonplanar features of nanofabricated fin‐like projections with characteristic length scales of ≈100 nm can substantially increase the interfacial heat flow through an increase in the overall contact area . Similarly, MD studies have also shown that these types of features (even down to sub‐nanometer length scales) can be used to achieve an increase in h K .…”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
See 3 more Smart Citations